Pengembangan E-modul Berbasis Pendekatan Saintifik Pada Materi Hidrolisis Garam Untuk Siswa Kelas XI SMA/MA - Sari, Setri Delvita (journal of residu, 2019)
The type of research that used in this study is Research and Development (R&D) by using 4D development model (four D models). This study aims to produce an e-module based on the scientific approach on salt hydrolysis for students of XI grade SMA/MA and to determine the level of validity and practicality of the e-module that has been produced. The instrument used in this study is a questionnaire of validity and practicality. The validity test were carried out by 3 chemistry lecturers and 2 chemistry teacher, while the practicality test was carried out on 30 students of XII grade IPA 1 of SMAN 1 Padang and 2 chemistry teachers of SMAN 12 Padang. From the results of data processing, the average kappa moment of the validity is 0,87 with a very high level of validity. While the practicality test obtained the average kappa moment of 0,88 both are from the teacher questionnaire and from the student questionnaire with a very high level of practicality. There for, an e-module based on a scientific approach has been produced in the salt hydrolysis materials for students of XI grade SMA/MA that is valid and practical.